2014
DOI: 10.1007/s00586-014-3507-4
|View full text |Cite
|
Sign up to set email alerts
|

Results after the surgical treatment of anterior cervical hyperostosis causing dysphagia

Abstract: Diffuse idiopathic skeletal hyperostosis may lead to osteophyte-associated pathologies of the aerodigestive tract. Preoperative investigations with esophageal and laryngoscopic examinations combined with fluoroscopic swallowing tests are essential. Surgical decompression through osteophytectomy and fusion is an effective management strategy in selected patients and should be considered when non-operative strategies have failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 21 publications
1
55
0
Order By: Relevance
“…4,22,23 When the extrinsic cause of the compression is the most prominent, surgical resection of the osteophytes via a standard anterior approach can be performed for more severe conditions and impairment of the quality of life. 4,[24][25][26][27][28] The results are less satisfactory the more the changes in the esophagus itself have progressed. 4,29 The resection of the osteophytes does not eliminate the underlying disease, so new ossification can develop.…”
Section: Introductionmentioning
confidence: 99%
“…4,22,23 When the extrinsic cause of the compression is the most prominent, surgical resection of the osteophytes via a standard anterior approach can be performed for more severe conditions and impairment of the quality of life. 4,[24][25][26][27][28] The results are less satisfactory the more the changes in the esophagus itself have progressed. 4,29 The resection of the osteophytes does not eliminate the underlying disease, so new ossification can develop.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have insisted that appropriate management of this condition requires cervical fusion 12,23) , as ligamentous ossification 10 is believed to progress until rigidity is established. Nicolas H et al also reported six cases of osteophytectomy and fusion 24) . However, the possibility of adjacent segment osteophyte development after fusion surgery remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…The size of the osteophyte does not correlate with the severity of dysphagia, although it is commonly accepted that bone a excrescence bigger than 12mm becomes a symptomatic, but bigger than 10mm increases significantly the risk of aspiration [18,19]. Gradually increasing dysphagia symptoms worsen the quality of a patient's life, and 8-10% of cases require surgical treatment [15,20].…”
Section: Discussionmentioning
confidence: 99%